Embolic Stroke as the Initial Manifestation of Systemic Lupus Erythematosus - Reshma M. Khan; Rajaie Namas; Sachin Parikh; Bernard Rubin (Case Reports in Rheumatology)
We present a case of a 21-year-old African-American female with no significant medical history, who presented to the emergency department with a one-week history of blurry and double vision. Ophthalmology evaluation revealed bilateral retinal artery occlusion. Further workup with imaging of the brain was consistent with an ischemic stroke. Hereditary hypercoagulable workup was unremarkable and initial testing for antiphospholipid syndrome was positive. She underwent transesophageal echocardiogram (TEE), which showed severe mitral regurgitation and thickening of mitral valve leaflets consistent with Libman-Sacks endocarditis. Autoimmune workup was positive for IF-ANA, anti-RNP, and anti-Smith antibody. She fulfilled 4/11 of the ACR criteria and met 5 of the SLICC (Systemic Lupus International Collaborating Clinics) criteria for lupus (nonscaring alopecia, thrombocytopenia, positive ANA, and positive anti-Smith and positive anti-phospholipid antibodies). This case highlights the importance of early recognition of underlying connective tissue diseases and timely management of these diseases in young patients with no previous manifestations of diseases.